Socio-economic linkages of COVID -19 Pandemic - Joshi, Yashwi; Mishra, Prof. Anand Prasad (National Geographical Journal of India, 2022)
Despite being collective human tragedies on exceptional scales, the pandemics due to their long recurrence periods generally remain marginalized in the mainstream discourse of human geography. Throughout history, it has taken an overwhelming pandemic like COVID-19 or the Spanish u at the beginning of the last century to bring the academic discussion on pandemics to the centre stage. Due to compartmentalization of thought, the socioeconomic linkages of pandemic largely remain obscure to the common people and even intellectuals engaged in other disciplines. The paper outlines how overexploitation of the earth resources through commodity supply chains is responsible for the spread of the COVID-19 pandemic all over the world. The reckless plunder of remotest countryside and forests by the neoliberal economy essentially works at valorization of the capital by over exploiting both nature and people in the global South, to siphon all the surplus-value to the global North through complex chains of commodity circuits. The neoliberal socio-economic structure is even otherwise virtually free in principle not to take any responsibility for either the health or employment of the majority of common people. Once the world is overtaken by the pandemic this lack of responsibility becomes glaring. The suggestions for creating an infrastructure for health services made shortly before the Indian independence that was followed in the initial decades after 1947 have now been relegated to the background with the private sector making ever more inroads in the health sector, further depriving the common man of the minimal requisite medical facilities. As the COVID-19 pandemic has brought out the real face of the existing socioeconomic structure in its failure and refusal to assume any responsibility for the basic needs of the people like food and shelter, the time is ripe to contemplate better alternative systems that could be more pro-people